READING DURKHEIM THROUGH OTTOMAN LENSES: INTERPRETATIONS OF CUSTOMARY LAW, RELIGION, AND SOCIETY BY THE SCHOOL OF GOKALP - Ozervarli, M. Sait (CAMBRIDGE UNIV PRESS, 2017)
This article focuses on how late Ottoman intellectuals selectively read the sociologist Emile Durkheim and used his thoughts to rediscover and reform their own classical, normative Islamic and social theories. Emile Durkheim, a late nineteenth- and early twentieth-century French thinker who combined philosophy with social and political issues, powerfully inspired one of the late Ottoman intellectual circles that aimed to provide theoretical underpinnings for a significant transformation of Turkish society. The article takes a closer look at the school of Ziya Gokalp, the acknowledged pioneer of social thought in Turkey, highlighting also lesser-known works of some of his followers, and how they perceivedin distinct waysDurkheim's views in a Gokalpian manner, seeking a new synthesis with Islamic legal and religious interpretations to modernize their society in connection with the past. It thus explores some creative Ottoman appropriations of Durkheimian methodology for a different cultural environment.
Keywords: EMILE DURKHEIM; History